Essential oils extracted from Phoebe hui Cheng ex Yang: Chemical constituents, antitumor and antibacterial activities, and potential use as a species identifier. (4th May 2017) - Ding, Wen; Ning, Liping; Xiong, Yan; Shi, Hao; Wang, Tianshi; An, Rongmiao
Abstract : The essential oils in Phoebe hui Cheng ex Yang were extracted from its roots, trunk, bark, branches, and leaves by a hydrothermal method and then analyzed by gas chromatography–mass spectrometry. The essential oils extracted from the xylem of the roots and trunks of this species had similar chemical constituents (primarily α-bergamotene, calarene, 3, 7-guaiadiene, β-sesquiphellandrene, β-farnesene, β-bisabolene, torreyol, and τ-muurolol) in similar quantities. Meanwhile, the main chemical constituents of the essential oil extracted from the xylem of this species were considerably different from those extracted from Phoebe zhennan . Hence, analysis of the oils extracted from the xylem can be used to distinguish between these species. The essential oils extracted from the bark, branches, and leaves of P. hui Cheng ex Yang had identical chemical constituents. The bark oil comprised mainly cubebene, α-muurolene, δ-cadinene, cadina-1, 4-diene, guaiol, δ-cadinol, and α-cadinol, whereas the branch oil mainly included cubebene, α-selinene, δ-cadinene, cadina-1, 4-diene, guaiol, δ-cadinol, and α-cadinol. The leaf oil extract consisted of cyclosativene, γ-muurolene, β-selinene, α-selinene, γ-cadinene, δ-cadinene, δ-cadinol, γ-eudesmol, α-cadinol, β-eudesmol, and α-eudesmol. Although the antimicrobial effects of the essential oils extracted from the individual tree parts were unclear, a mixture of these oils exhibited significant antitumor properties.